2015
DOI: 10.1152/ajpendo.00441.2014
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle insulin resistance in zebrafish induces alterations in β-cell number and glucose tolerance in an age- and diet-dependent manner

Abstract: Maddison LA, Joest KE, Kammeyer RM, Chen W. Skeletal muscle insulin resistance in zebrafish induces alterations in ␤-cell number and glucose tolerance in an age-and diet-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 40 publications
0
60
0
Order By: Relevance
“…In addition, variants of upstream, downstream, and intronic regions of the immunoglobulin heavy chain variable ( IGHV ) gene were annotated. Interesting, this gene has been reported to be the most important indicator of chronic lymphocytic leukemia prognosis48. Although the tambaqui genome sequences are still not available, comparative genome analysis enabled the identification of large number of markers in genic regions, which in turn could be used in tambaqui breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, variants of upstream, downstream, and intronic regions of the immunoglobulin heavy chain variable ( IGHV ) gene were annotated. Interesting, this gene has been reported to be the most important indicator of chronic lymphocytic leukemia prognosis48. Although the tambaqui genome sequences are still not available, comparative genome analysis enabled the identification of large number of markers in genic regions, which in turn could be used in tambaqui breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to mouse models, diet induced obesity in the zebrafish increases serum triglycerides and hepatic lipid accumulation 12 . Furthermore, overfed zebrafish have elevated fasting glucose, suggesting glucose intolerance 14 . Using the assay described here we have shown that 24 hr of pretreatment with Metformin, an insulin sensitizer, increases the metabolic rate response to insulin treatment 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Akt signaling plays a central role in insulin-stimulated glucose uptake in peripheral tissues in both mammals and zebrafish 43,44 ; therefore, we examined if insulin-mediated Akt phosphorylation was affected by genetic deletion of gpr27. Akt signaling plays a central role in insulin-stimulated glucose uptake in peripheral tissues in both mammals and zebrafish 43,44 ; therefore, we examined if insulin-mediated Akt phosphorylation was affected by genetic deletion of gpr27.…”
Section: Loss Of Gpr27 Abrogates Akt-dependent Insulin Signalingmentioning
confidence: 99%
“…We next sought to determine if there was a defect in insulin signaling in gpr27 KO zebrafish. Akt signaling plays a central role in insulin-stimulated glucose uptake in peripheral tissues in both mammals and zebrafish 43,44 ; therefore, we examined if insulin-mediated Akt phosphorylation was affected by genetic deletion of gpr27. Following a 2-h incubation period, lysates were generated and subjected to Western blotting for p-Akt (Ser473) and total Akt ( Figure 4D-E).…”
Section: Loss Of Gpr27 Abrogates Akt-dependent Insulin Signalingmentioning
confidence: 99%